2011
DOI: 10.4149/neo_2011_03_211
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of B cell-activating factor (BAFF) in neutrophils of oral cavity cancer patients – preliminary study

Abstract: In the present study the expression of tumor-promoting B cell-activating factor (BAFF), a member of the tumor necrosis factor superfamily (TNF) in neutrophils from oral cavity cancer patients, was examined by real-time PCR. For the purpose of comparison, the expression of BAFF protein was assessed in autologous peripheral blood mononuclear cells (PBMCs). An important question of this study has also been to explain the role of NF-κB in the induction of BAFF molecule. The increased expression of BAFF at the mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A number of clinical and experimental studies have focused on the measurement of cytokine expression as parameters of the immune potential of cancer patients. Available data, including our own observations, indicate that the production of cytokines by human neutrophils may have different effects on tumor development [7,8,10,11].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A number of clinical and experimental studies have focused on the measurement of cytokine expression as parameters of the immune potential of cancer patients. Available data, including our own observations, indicate that the production of cytokines by human neutrophils may have different effects on tumor development [7,8,10,11].…”
Section: Discussionmentioning
confidence: 82%
“…Our previous study, carried out in patients with OCSCC, revealed unfavorable features of peripheral blood neutrophils, associated with changes in the release of some proteins belonging to the tumor necrosis factor (TNF) superfamily. The high secretion of soluble TNFRp75 receptor that can limit the availability of TNF-␣ and deficit of tumor-inhibiting TNF-related apoptosisinducing ligand (TRAIL), in addition to overexpression of tumor-promoting B cell-activating factor (BAFF/Blys) in these cells, may facilitate tumor development in patients with OSCC [10][11][12]. Studies by Mhawech et al [13] in patients with OCSCC, suggested that tumor-infiltrating neutrophils are the main source of another TNF-superfamily ligand, i.e.…”
mentioning
confidence: 99%
“…We identified Gr1 + infiltrating neutrophils as an important source of BAFF in mouse fibrotic lungs.Human neutrophils were shown to release biologically active BAFF after in vitro incubation with G-CSF [39]. BAFF is produced by tissue infiltrating human neutrophils or bone marrow neutrophils in several diseases [23,[40][41][42][43][44]. BAFF secreted by inflammatory neutrophils has been implicated in B-cell, but not in T-cell, responses in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The current conceptual picture posits BAFF and APRIL as primarily pathogenic players in microenvironments of both solid and hematological tumors. Elevated serum BAFF levels derived from neutrophils have been noted in oral cavity cancers [46], have been associated with promoting invasive migration activity in hypoxic breast cancer cell line studies [47], and correlated with increased serum TNF levels, angiogenesis and poor prognosis in multiple myeloma [48]. Overexpression of BAFF has been shown to enhance c-myc expression and promote chronic lymphocytic leukemia (CLL)-like disease via activation of the canonical IKK in Myc/BAFF Tg mice [49].…”
Section: The Role Of the Baff System In Cancermentioning
confidence: 99%